The Persistence of Union Membership within the Coalfields of Britain - Huw Beynon; Helen Blakely; Alex Bryson; Rhys Davies (Institute of Labor Economics (IZA), 2020)
Spatial variance in union membership has been attributed to the favourable attitudes that persist in areas with an historical legacy of trade unionism. Within the UK, villages and towns located in areas once dominated coalmining remain among the strongest and durable bases for the trade union movement. This paper empirically examines the effect of living within or near these areas upon union membership. Those residing in ex-mining areas retain an increased propensity for union membership. However, this effect diminishes sharply with distance. The analysis reveals that particular places can serve as conduits of trade unionism, long after employment within traditional industries has vanished.
Keywords: J50; J51; 330; union membership; spatial variance; spill-over; coalmining